Peningkatan Asuhan Kemandirian Penggunaan Tanaman Obat Pada Kader PKK di Dusun Pucung Kranggan II Berbah Sleman Yogyakarta - Arde Toga Nugraha; Asih Triastuti (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
This service activity aims to provide independent care for the use of medicinal plants and traditional medicines as a promotional and preventive effort, which is beneficial for the efficiency and effectiveness of families in maintaining the family health. Independent care is built in the form of a cadre of TAMAWA (Tanam-Manfaat-Waspada/Grow-Use-Alert) frameworks of medicinal plants and traditional medicines, the participants of which are PKK in the village of Pucung Kranggan II. The TAMAWA cadres were formed in each neighbourhood association /RT, with four members per RT. The TAMAWA framework was formed and guided by a community service team, in collaboration with the Center for Herbal Medicine Study (PSOH UII) of the Department of Pharmacy, Universitas Islam Indonesia through several activities, including training in traditional medicinal/medicinal plants, training in traditional medicinal recipes, and the built of a family medicinal plant garden (TOGA). The output of this service is the production of a smartbook for TAMAWA cadres containing the types, benefits, usage preparations, drug interactions and side effects of medicinal plants/traditional medicines and the built of  TOGA gardens in each RT in the village. Other outputs have also been produced, such as information media in the form of videos and brochures. It is hoped that this service program will increase public knowledge of medicinal plants/traditional medicines. Also, it is hoped that the community will be more independent and empowered to manage daily health